BAHASA VIETNAM SEBAGAI BAHASA NADA - . Hendrokumoro (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
Vietnamese is a complex language as evidenced by the variety of its tones, shapes and meanings. Its complexity is a natural result of the fact that the language belongs to different proto-languages, i.e. Austro-Asiatic, Sino- Tibet, Thai-Kadai and Hmong-Dao. Therefore, it is interesting to study Vietnamese. Vietnamese is a tonal language. Pitch is a crucial part in tonal languages since it helps create suprasegmental phonemes to produce different lexical meaning. To understand suprasegmental phonemes, one must understand segmental phonemes. A tonal analysis can only be done after efforts have been made to reveal segmental phonemes. This article attempts to answer these questions: (1) how to describe the Vietnamese phonological system, and (2) how to describe pitch in a tonal language such as Vietnamese. While the Vietnamese phonological system makes up the segmental phonemes, pitch in Vietnamese language makes up the suprasegmental phonemes.